Unequal Climate Policy in an Unequal World - Elisa Belfiori; Daniel Carroll; Sewon Hur (Munich Society for the Promotion of Economic Research - CESifo GmbH, 2026)
We characterize optimal climate policy in an economy with heterogeneous households and non-homothetic preferences. We focus on constrained efficiency, where the planner is restricted from transferring resources across households. We derive three results. First, the constrained-optimal carbon tax is heterogeneous and progressive. Second, if restricted to a uniform tax, the optimal rate is lower than the standard Pigouvian level due to inequality. Third, this allocation is decentralizable using only uniform instruments - a carbon tax, clean subsidy, and a lumpsum transfer. In a quantitative application, we show this policy generates a Pareto improvement, reconciling climate efficiency with inequality concerns.
Keywords: E21; H21; H23; Q54; 330; carbon tax; inequality; consumption; welfare; climate change